Foscan and foslip based photodynamic therapy in osteosarcoma in vitro and in intratibial mouse models. Issue 7 (1st April 2017) - Meier, Daniela; Botter, Sander M.; Campanile, Carmen; Robl, Bernhard; Gräfe, Susanna; Pellegrini, Giovanni; Born, Walter; Fuchs, Bruno
Abstract : Current osteosarcoma therapies cause severe treatment‐related side effects and chemoresistance, and have low success rates. Consequently, alternative treatment options are urgently needed. Photodynamic therapy (PDT) is a minimally invasive, local therapy with proven clinical efficacy for a variety of tumor types. PDT is cytotoxic, provokes anti‐vascular effects and stimulates tumor cell targeting mechanisms of the immune system and, consequently, has potential as a novel therapy for osteosarcoma patients. This study investigated the uptake and the dark‐ and phototoxicity and cytotoxic mechanisms of the photosensitizer (PS) 5, 10, 15, 20‐tetrakis(meta‐hydroxyphenyl) chlorine (mTHPC, Foscan) and a liposomal mTHPC formulation (Foslip) in the human 143B and a mouse K7M2‐derived osteosaroma cell line (K7M2L2) in vitro . Second, the tumor‐ and metastasis‐suppressive efficacies of mTHPC formulations based PDT and associated mechanisms in intratibial, metastasizing osteosarcoma mouse models (143B/SCID and syngeneic K7M2L2/BALB/c) were studied. The uptake of Foscan and Foslip in vitro was time‐ and dose‐dependent and resulted in mTHPC and light dose‐dependent phototoxicity associated with apoptosis. In vivo, the uptake of both i.v. administered mTHPC formulations was higher in tumor than in healthy control tissue. PDT caused significant (Foscan p < 0.05, Foslip p < 0.001) tumor growth inhibition in both models. A significant (Foscan p < 0.001, Foslip p < 0.001) immune system‐dependent suppression of lung metastasis was only observed in the K7M2L2/BALB/c model and was associated with a marked infiltration of T‐lymphocytes at the primary tumor site. In conclusion, mTHPC‐based PDT is effective in clinically relevant experimental osteosarcoma and suppresses lung metastasis in immunocompetent mice with beneficial effects of the liposomal mTHPC formulation Foslip. Abstract : What's new? Photodynamic therapy (PDT) is a promising cancer treatment based on the local light application after systemic photosensitizer injection. Here the authors tested a specific photosensitizer, Foscan and its liposomal formulation Foslip in two mouse models of osteosarcoma. PDT inhibited tumor growth and suppressed immune system‐dependent metastatic spread, supporting a potential clinical application of PDT to children or adolescents affected with osteosarcoma in the future.